ORGANIZATIONAL AND ECONOMIC PRINCIPLES OF THE DEVELOPMENT OF COOPERATION IN THE MILK MARKET IN UKRAINE UNDER THE CONDITIONS OF EUROPEAN INTEGRATION - IBATULLIN, Marat; HRYVKIVSKA, Oksana; KARPENKO, Vitalii; SVINOUS, Nadia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
When considering the issue of cooperation between counterparties of agri-food supply chains, it is advisable to pay attention to the peculiarities of the formation of economic relations at both the horizontal and vertical levels. It is obvious that the drivers of the formation of long-term partnership relations should be processing enterprises, since they are the ones experiencing a shortage of raw materials, but they have no interest in receiving agricultural raw materials from smaller and scattered small commodity producers. On the other hand, end consumers demand agri-food products that have the appropriate quality, origin and certified production process. It is these factors that require the development of effective tools for the development of transparent and mutually beneficial economic relations in horizontal and vertical agri-food supply chains. The article is devoted to the problems of the development of cooperation in the production of milk in Ukraine. It was found that when forming integrated structures of agricultural producers and processing enterprises in the dairy sub-complex, it is important to take into account the economic interests of future partners to ensure their mutually beneficial and sustainable production activities. A mathematical toolkit for modeling the production activity of an agricultural service cooperative, jointly formed by small agricultural commodity producers and processing enterprises, has been developed, which adequately reflects the real economic conditions of the SOK. It has been proven that the development of cooperative structures at the regional level can be ensured according to the principle of associated cooperation with the participation of large trade networks, under the condition of public-private partnership with a high state share, or under the condition of the contribution of the united territorial rural community. The proposed system of cooperative networks can be organized gradually or partially, with the initial formation of pilot projects in individual regions. As alternatives, the following pilot scenarios for the formation of cooperative centers are proposed: single - the creation of one most effective cooperative center with the minimum investment payback period is envisaged; distribution - it is envisaged to create one cooperative center for each type of product; concentrated - involves placing as many centers as possible in rural areas with the aim of creating local growth points.